Ginkgolide B Protects Cardiomyocytes from Angiotensin II-Induced Hypertrophy via Regulation of Autophagy through SIRT1-FoxO1 - Qingyuan Jiang; Ming Lu; Jinyu Li; Zhongsheng Zhu (Hindawi-Wiley, 2021)
Ginkgolide B (GB) is an active ingredient extracted from Ginkgo biloba leaves. However, the effects of GB on cardiac hypertrophy remain unclear. The study is aimed at determining whether GB could alleviate cardiac hypertrophy and exploring its underlying molecular mechanism. Rat cardiomyocyte cell line H9c2 cells were pretreated with GB and incubated with angiotensin II (Ang II) to simulate an in vitro cardiac hypertrophy model. Cell viability, cell size, hypertrophy markers, and autophagy were determined in H9c2 cells after Ang II treatment. Proteins involved in autophagy and the SIRT1 pathway were determined by western blot. Our data demonstrated that GB attenuated Ang II-induced cardiac hypertrophy and reduced the mRNA expressions of hypertrophy marker, atrial natriuretic peptide (ANP), and β-myosin heavy chain (β-MHC). GB further increased Ang II-induced autophagy in H9c2 cells and modulated expressions of autophagy-related proteins Beclin1 and P62. Modulation of autophagy using autophagy inhibitor 3-methyladenine (3-MA) could abrogate GB-downregulated transcription of NPPA. We then showed that GB attenuated Ang II-induced oxidative stress and reduction in SIRT1 and FoxO1 protein expression. Finally, the effect of GB on autophagy and cardiac hypertrophy could be reversed by SIRT1 inhibitor EX-527. GB inhibits Ang II-induced cardiac hypertrophy by enhancing autophagy via the SIRT1-FoxO1 signaling pathway and might be a potential agent in treating pathological cardiac hypertrophy.